Pregunta
upstudy study bank question image url

36 Résoudre dans \( \mathbb{R} \times \mathbb{R} \) les systèmes d'équations suivants : (1) \( \left\{\begin{aligned} x+y & =-1 \\ x y & =-1\end{aligned}\right. \) (4) \( \left\{\begin{aligned} \frac{x^{2}}{y}+\frac{y^{2}}{x} & =0 \\ x y & =-1\end{aligned}\right. \) (2) \( \left\{\begin{aligned} x^{2}+y^{2} & =5 \\ x y & =-2\end{aligned}\right. \) (5) \( \left\{\begin{aligned} x^{4}+y^{4} & =17 \\ x y & =2\end{aligned}\right. \) (3) \( \left\{\begin{array}{l}x^{2}+y^{2}=20 \\ \frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{array}\right. \) (6) \( \left\{\begin{aligned} x-y & =2 \\ x y & =35\end{aligned}\right. \) 37 Résoudre dans \( \mathbb{R} \) les équations suivantes : (1) \( 2 x|x|-6 x-2=0 \); (2) \( 2 x^{2}-3 x+5=|x-1| \) 38 On considère l'équation :

Ask by Garrett Nunez. in Gabon
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Voici les solutions simplifiées pour les systèmes d'équations et les équations demandées : ### Systèmes d'équations 1. \( x + y = -1 \) et \( x y = -1 \): - Solutions: \( (x, y) = (-1, 1) \) et \( (1, -1) \) 2. \( \frac{x^2}{y} + \frac{y^2}{x} = 0 \) et \( x y = -1 \): - Solutions: \( (x, y) = (-1, 1) \) et \( (1, -1) \) 3. \( x^2 + y^2 = 5 \) et \( x y = -2 \): - Solutions: \( (x, y) = (-1, 2) \), \( (-2, 1) \), \( (1, -2) \), \( (2, -1) \) 4. \( x^4 + y^4 = 17 \) et \( x y = 2 \): - Solutions: \( (x, y) = (-1, -2) \), \( (-2, -1) \), \( (1, 2) \), \( (2, 1) \) 5. \( x^2 + y^2 = 20 \) et \( \frac{x}{y} + \frac{y}{x} = \frac{5}{2} \): - Solutions: \( (x, y) = (-2, -4) \), \( (-4, -2) \), \( (2, 4) \), \( (4, 2) \) 6. \( x - y = 2 \) et \( x y = 35 \): - Solutions: \( (x, y) = (-5, -7) \) et \( (7, 5) \) ### Équations 1. \( 2 x|x| - 6 x - 2 = 0 \): - Solutions: \( x = -\frac{3 + \sqrt{5}}{2} \), \( x = \frac{-3 + \sqrt{5}}{2} \), \( x = \frac{3 + \sqrt{13}}{2} \) 2. \( 2 x^2 - 3 x + 5 = |x - 1| \): - Aucune solution réelle Si vous avez besoin de plus d'informations ou d'autres questions, n'hésitez pas à demander !

Solución

Solve the equation by following steps: - step0: Solve for \(x\): \(2x^{2}-3x+5=\left|x-1\right|\) - step1: Move the expression to the left side: \(2x^{2}-3x+5-\left|x-1\right|=0\) - step2: Separate into possible cases: \(\begin{align}&2x^{2}-3x+5-\left(x-1\right)=0,x-1\geq 0\\&2x^{2}-3x+5-\left(-\left(x-1\right)\right)=0,x-1<0\end{align}\) - step3: Solve the equation: \(\begin{align}&x \notin \mathbb{R},x\geq 1\\&x \notin \mathbb{R},x<1\end{align}\) - step4: Find the intersection: \(\begin{align}&x \notin \mathbb{R}\\&x \notin \mathbb{R}\end{align}\) - step5: Find the union: \(x \notin \mathbb{R}\) Solve the system of equations \( x^{4}+y^{4}=17;xy=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{4}+y^{4}=17\\xy=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{4}+y^{4}=17\\x=\frac{2}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(\frac{2}{y}\right)^{4}+y^{4}=17\) - step3: Simplify: \(\frac{16+y^{8}}{y^{4}}=17\) - step4: Cross multiply: \(16+y^{8}=y^{4}\times 17\) - step5: Simplify the equation: \(16+y^{8}=17y^{4}\) - step6: Move the expression to the left side: \(16+y^{8}-17y^{4}=0\) - step7: Factor the expression: \(\left(2-y\right)\left(1-y\right)\left(1+y\right)\left(2+y\right)\left(1+y^{2}\right)\left(4+y^{2}\right)=0\) - step8: Separate into possible cases: \(2-y=0\cup 1-y=0\cup 1+y=0\cup 2+y=0\cup 1+y^{2}=0\cup 4+y^{2}=0\) - step9: Solve the equation: \(y=2\cup y=1\cup y=-1\cup y=-2\cup y \notin \mathbb{R}\cup y \notin \mathbb{R}\) - step10: Find the union: \(y=2\cup y=1\cup y=-1\cup y=-2\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2}{y}\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=-2\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-1,-2\right)\cup \left(x,y\right) = \left(-2,-1\right)\cup \left(x,y\right) = \left(1,2\right)\cup \left(x,y\right) = \left(2,1\right)\) Solve the system of equations \( x-y=2;xy=35 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x-y=2\\xy=35\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2+y\\xy=35\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(2+y\right)y=35\) - step3: Simplify: \(y\left(2+y\right)=35\) - step4: Expand the expression: \(2y+y^{2}=35\) - step5: Move the expression to the left side: \(2y+y^{2}-35=0\) - step6: Factor the expression: \(\left(y-5\right)\left(y+7\right)=0\) - step7: Separate into possible cases: \(\begin{align}&y-5=0\\&y+7=0\end{align}\) - step8: Solve the equation: \(\begin{align}&y=5\\&y=-7\end{align}\) - step9: Calculate: \(y=5\cup y=-7\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=2+y\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=2+y\\y=-7\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-5,-7\right)\cup \left(x,y\right) = \left(7,5\right)\) Solve the equation \( 2x|x|-6x-2=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2x\left|x\right|-6x-2=0\) - step1: Separate into possible cases: \(\begin{align}&2x\times x-6x-2=0,x\geq 0\\&2x\left(-x\right)-6x-2=0,x<0\end{align}\) - step2: Solve the equation: \(\begin{align}&\begin{align}&x=\frac{3+\sqrt{13}}{2}\\&x=\frac{3-\sqrt{13}}{2}\end{align},x\geq 0\\&\begin{align}&x=\frac{-3+\sqrt{5}}{2}\\&x=-\frac{3+\sqrt{5}}{2}\end{align},x<0\end{align}\) - step3: Find the intersection: \(\begin{align}&x=\frac{3+\sqrt{13}}{2}\\&x=\frac{-3+\sqrt{5}}{2}\\&x=-\frac{3+\sqrt{5}}{2}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{3+\sqrt{5}}{2},x_{2}=\frac{-3+\sqrt{5}}{2},x_{3}=\frac{3+\sqrt{13}}{2}\) Solve the system of equations \( x^{2}+y^{2}=20;\frac{x}{y}+\frac{y}{x}=\frac{5}{2} \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\\frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=\frac{y}{2}\cup x=2y\end{array}\right.\) - step2: Evaluate: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=\frac{y}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=2y\end{array}\right.\) - step3: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step4: Rearrange the terms: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step5: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step6: Rewrite: \(\left(x,y\right) = \left(-2,-4\right)\cup \left(x,y\right) = \left(-4,-2\right)\cup \left(x,y\right) = \left(2,4\right)\cup \left(x,y\right) = \left(4,2\right)\) Solve the system of equations \( \frac{x^{2}}{y}+\frac{y^{2}}{x}=0;xy=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}\frac{x^{2}}{y}+\frac{y^{2}}{x}=0\\xy=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}\frac{x^{2}}{y}+\frac{y^{2}}{x}=0\\x=-\frac{1}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\frac{\left(-\frac{1}{y}\right)^{2}}{y}+\frac{y^{2}}{-\frac{1}{y}}=0\) - step3: Simplify: \(\frac{1}{y^{3}}-y^{3}=0\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{1}{y^{3}}-y^{3}\right)y^{3}=0\times y^{3}\) - step5: Simplify the equation: \(1-y^{6}=0\) - step6: Rewrite the expression: \(-y^{6}=-1\) - step7: Change the signs: \(y^{6}=1\) - step8: Simplify the expression: \(y=\pm \sqrt[6]{1}\) - step9: Simplify: \(y=\pm 1\) - step10: Separate into possible cases: \(y=1\cup y=-1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=-\frac{1}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{1}{y}\\y=-1\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,1\right)\cup \left(x,y\right) = \left(1,-1\right)\) Solve the system of equations \( x+y=-1;xy=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y=-1\\xy=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-1-y\\xy=-1\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(-1-y\right)y=-1\) - step3: Simplify: \(y\left(-1-y\right)=-1\) - step4: Expand the expression: \(-y-y^{2}=-1\) - step5: Move the expression to the left side: \(-y-y^{2}-\left(-1\right)=0\) - step6: Remove the parentheses: \(-y-y^{2}+1=0\) - step7: Rewrite in standard form: \(-y^{2}-y+1=0\) - step8: Multiply both sides: \(y^{2}+y-1=0\) - step9: Solve using the quadratic formula: \(y=\frac{-1\pm \sqrt{1^{2}-4\left(-1\right)}}{2}\) - step10: Simplify the expression: \(y=\frac{-1\pm \sqrt{5}}{2}\) - step11: Separate into possible cases: \(\begin{align}&y=\frac{-1+\sqrt{5}}{2}\\&y=\frac{-1-\sqrt{5}}{2}\end{align}\) - step12: Rewrite the fraction: \(\begin{align}&y=\frac{-1+\sqrt{5}}{2}\\&y=-\frac{1+\sqrt{5}}{2}\end{align}\) - step13: Evaluate the logic: \(y=\frac{-1+\sqrt{5}}{2}\cup y=-\frac{1+\sqrt{5}}{2}\) - step14: Rearrange the terms: \(\left\{ \begin{array}{l}x=-1-y\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-y\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step15: Calculate: \(\left\{ \begin{array}{l}x=-\frac{1+\sqrt{5}}{2}\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{-1+\sqrt{5}}{2}\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step16: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{1+\sqrt{5}}{2}\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{-1+\sqrt{5}}{2}\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step17: Rewrite: \(\left(x,y\right) = \left(-\frac{1+\sqrt{5}}{2},\frac{-1+\sqrt{5}}{2}\right)\cup \left(x,y\right) = \left(\frac{-1+\sqrt{5}}{2},-\frac{1+\sqrt{5}}{2}\right)\) Solve the system of equations \( x^{2}+y^{2}=5;xy=-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}+y^{2}=5\\xy=-2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}+y^{2}=5\\x=-\frac{2}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(-\frac{2}{y}\right)^{2}+y^{2}=5\) - step3: Simplify: \(\frac{4+y^{4}}{y^{2}}=5\) - step4: Cross multiply: \(4+y^{4}=y^{2}\times 5\) - step5: Simplify the equation: \(4+y^{4}=5y^{2}\) - step6: Move the expression to the left side: \(4+y^{4}-5y^{2}=0\) - step7: Factor the expression: \(\left(2-y\right)\left(1-y\right)\left(1+y\right)\left(2+y\right)=0\) - step8: Separate into possible cases: \(2-y=0\cup 1-y=0\cup 1+y=0\cup 2+y=0\) - step9: Solve the equation: \(y=2\cup y=1\cup y=-1\cup y=-2\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=-\frac{2}{y}\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=-2\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,2\right)\cup \left(x,y\right) = \left(-2,1\right)\cup \left(x,y\right) = \left(1,-2\right)\cup \left(x,y\right) = \left(2,-1\right)\) Voici les solutions pour les systèmes d'équations et les équations demandées : ### Systèmes d'équations 1. Pour le système \( \left\{\begin{aligned} x+y & =-1 \\ x y & =-1\end{aligned}\right. \): - Solutions : \[ (x,y) = \left(-\frac{1+\sqrt{5}}{2}, \frac{-1+\sqrt{5}}{2}\right) \cup (x,y) = \left(\frac{-1+\sqrt{5}}{2}, -\frac{1+\sqrt{5}}{2}\right) \] 2. Pour le système \( \left\{\begin{aligned} \frac{x^{2}}{y}+\frac{y^{2}}{x} & =0 \\ x y & =-1\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,1) \cup (x,y) = (1,-1) \] 3. Pour le système \( \left\{\begin{aligned} x^{2}+y^{2} & =5 \\ x y & =-2\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,2) \cup (x,y) = (-2,1) \cup (x,y) = (1,-2) \cup (x,y) = (2,-1) \] 4. Pour le système \( \left\{\begin{aligned} x^{4}+y^{4} & =17 \\ x y & =2\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,-2) \cup (x,y) = (-2,-1) \cup (x,y) = (1,2) \cup (x,y) = (2,1) \] 5. Pour le système \( \left\{\begin{aligned} x^{2}+y^{2} & =20 \\ \frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{aligned}\right. \): - Solutions : \[ (x,y) = (-2,-4) \cup (x,y) = (-4,-2) \cup (x,y) = (2,4) \cup (x,y) = (4,2) \] 6. Pour le système \( \left\{\begin{aligned} x-y & =2 \\ x y & =35\end{aligned}\right. \): - Solutions : \[ (x,y) = (-5,-7) \cup (x,y) = (7,5) \] ### Équations 1. Pour l'équation \( 2 x|x|-6 x-2=0 \): - Solutions : \[ x_{1}=-\frac{3+\sqrt{5}}{2}, \quad x_{2}=\frac{-3+\sqrt{5}}{2}, \quad x_{3}=\frac{3+\sqrt{13}}{2} \] 2. Pour l'équation \( 2 x^{2}-3 x+5=|x-1| \): - Il n'y a pas de solution réelle : \[ x \notin \mathbb{R \text{ (pas de solution réelle)}} \] Si vous avez besoin de plus d'informations ou d'autres questions, n'hésitez pas à demander !

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

Vous avez là un tas d'équations à résoudre, prêt à vous faire briller comme un mathématicien étoilé ! En matière de systèmes d'équations, un bon point de départ est de réarranger les équations pour exprimer une variable en fonction d'une autre. Par exemple, dans le premier système, vous pouvez écrire \( y = -1 - x \) et le substituer dans l'autre équation. Cela facilite la recherche de solutions. Une erreur fréquente lors de la résolution de systèmes est d'oublier de vérifier la compatibilité des solutions trouvées. Une fois que vous avez un candidat pour \( x \) et \( y \), remplacez-le dans toutes les équations pour vous assurer qu'il fonctionne partout. Cela pourrait vous éviter des surprises désagréables à la fin de votre calcul !

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad